2010
DOI: 10.1128/jcm.00542-10
|View full text |Cite
|
Sign up to set email alerts
|

The Pan Genera Detection Immunoassay: a Novel Point-of-Issue Method for Detection of Bacterial Contamination in Platelet Concentrates

Abstract: Bacterial contamination of platelet concentrates (PCs) still represents an ongoing risk in transfusiontransmitted sepsis. Recently the Pan Genera Detection (PGD) system was developed and FDA licensed for screening of bacterial contamination of PCs directly prior to transfusion. The test principle is based on the immunological detection of lipopolysaccharide (for Gram-negative bacteria) or lipoteichoic acid (for Grampositive bacteria). In the present study we analyzed the applicability of this method with regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…Several methods for the detection of bacterial contamination in platelet concentrates (PCs) have been developed during the past decades, which can be divided into the different incubation/cultivation methods (BacT/ALERT system, bioMérieux; bactec system; VersaTrek system, Thermo Scientific) and direct detection of bacteria using rapid detection methods . Rapid‐detection methods include nucleic acid amplification techniques (NATs), fluorescence assorted cell sorting (e.g., BactiFlow [BF], bioMérieux), immunologic detection (PGD, Pan Genera Detection system [PGD]), or colorimetric assays (BacTx, Verax Biomedical) . Both methodological concepts were linked to different sampling strategies.…”
mentioning
confidence: 99%
“…Several methods for the detection of bacterial contamination in platelet concentrates (PCs) have been developed during the past decades, which can be divided into the different incubation/cultivation methods (BacT/ALERT system, bioMérieux; bactec system; VersaTrek system, Thermo Scientific) and direct detection of bacteria using rapid detection methods . Rapid‐detection methods include nucleic acid amplification techniques (NATs), fluorescence assorted cell sorting (e.g., BactiFlow [BF], bioMérieux), immunologic detection (PGD, Pan Genera Detection system [PGD]), or colorimetric assays (BacTx, Verax Biomedical) . Both methodological concepts were linked to different sampling strategies.…”
mentioning
confidence: 99%
“…using imaging instruments. However, it was demonstrated that currently used bacterial strains are capable to grow in PCs [8,12,13]. The comparison of results obtained with overnight grown cultures was proven to have no influence on the stability of bacterial cell counts and the result outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, for some Gram-negative strains the detection limit is greater than 10 6 CFU/ml [42]. Further disadvantages of the PGD assay are the costs, a high rate of false-positive results [23] and, currently, the subjective result interpretation [42]. This assay has been evaluated in various studies for use in quality control of PCs [43,44,45].…”
Section: Diagnostic Methods - Bacterial Screening Strategiesmentioning
confidence: 99%
“…The analytical sensitivity of this assay is specified as 10 3 -10 4 CFU/ml for Gram-positive bacteria and 10 3 -10 5 CFU/ml for Gram-negative bacteria. However, for some Gram-negative strains the detection limit is greater than 10 6 CFU/ml [42]. Further disadvantages of the PGD assay are the costs, a high rate of false-positive results [23] and, currently, the subjective result interpretation [42].…”
Section: Diagnostic Methods - Bacterial Screening Strategiesmentioning
confidence: 99%
See 1 more Smart Citation